Stimuli-Responsive Vesicles and Hydrogels Formed by a Single-Tailed Dynamic Covalent Surfactant in Aqueous Solutions - Chunlin Xu; Na Sun; Huaixiu Li; Xingchen Han; Ailing Zhang; Panpan Sun (Molecules)
Controlling the hierarchical self-assembly of surfactants in aqueous solutions has drawn much attention due to their broad range of applications, from targeted drug release, preparation of smart material, to biocatalysis. However, the synthetic procedures for surfactants with stimuli-responsive hydrophobic chains are complicated, which restricts the development of surfactants. Herein, a novel single-tailed responsive surfactant, 1-methyl-3-(2-(4-((tetradecylimino) methyl) phenoxy) ethyl)-3-imidazolium bromides (C14PMimBr), was facilely fabricated in situ by simply mixing an aldehyde-functionalized imidazolium cation (3-(2-(4-formylphenoxy) ethyl)-1-methyl imidazolium bromide, BAMimBr) and aliphatic amine (tetradecylamine, TDA) through dynamic imine bonding. With increasing concentration, micelles, vesicles, and hydrogels were spontaneously formed by the hierarchical self-assembly of C14PMimBr in aqueous solutions without any additives. The morphologies of vesicles and hydrogels were characterized by cryogenic transmission electron microscopy and scanning electron microscopy. The mechanical properties and microstructure information of hydrogels were demonstrated by rheological measurement, X-ray diffraction, and density functional theory calculation. In addition, the vesicles could be disassembled and reassembled with the breakage and reformation of imine bonds by adding acid/bubbling CO2 and adding alkali. This work provides a simple method for constructing stimuli-responsive surfactant systems and shows great potential application in targeted drug release, drug delivery, and intelligent materials.